Pretreatment method for high-strength and high-toughness lead screw and high-strength and high-toughness lead screw blank
Through the specific heat treatment method of high-nitrogen martensite stainless steel, the structure of the martensite matrix and residual austenite is formed, and the problem of taking into account both the lead screw strength and toughness is solved, and a high-strength and high-toughness screw blank is achieved. Meet the safety and corrosion resistance requirements of aircraft tail and wings.
Patent Information
- Application Number
- CN202411267824.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
AI Technical Summary
Existing lead screws are difficult to balance between strength and toughness and cannot be improved at the same time, especially in aircraft tail and wing applications, which require high strength and high toughness to meet safety and corrosion resistance.
High nitrogen martensite stainless steel rods are used for insulation and cooling, low temperature cooling treatment of -73±5℃ and tempering treatment of 550~650℃ to control various process parameters to form martensite matrix, residual austenite and trace amounts The structure of carbides.
It realizes a screw blank with both high strength and high toughness, with a core hardness of 38~41HRC, tensile strength ≥1150MPa, and no notch impact ≥150J, and is suitable for the manufacturing of high strength screws.
Smart Images

Figure CN119287128A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of screws, and in particular to a pretreatment method for a high-strength and tough screw and a high-strength and tough screw blank. Background Art
[0002] Aircraft lead screws are key components that ensure the movement of aircraft tail and wings. On the one hand, the lead screws are required to have high toughness in the core and high hardness on the surface to meet safety and fatigue resistance requirements; with the demand for aircraft applications in marine environments, aircraft tail and wing lead screws are required to have excellent corrosion resistance. Traditional steel materials such as 440C stainless steel can no longer meet the corrosion resistance requirements, and improvements and upgrades are needed from materials to heat treatment processes to increase the life and safety of the lead screws.
[0003] In the past 40 years, high-strength and high-hardness stainless steel has developed rapidly, from the initial 440C high-carbon chromium stainless steel (9Cr18 / 9Cr18Mo) to nitrogen-containing stainless high-strength steels such as X15ND, 440N2DUR and 30Cr15Mo1N. Among them, the surface hardness of high-nitrogen high-strength stainless steel 30Cr15Mo1N can reach more than 58HRC, and its corrosion resistance is more than 100 times higher than that of 440C, making it the champion steel with both high hardness and high corrosion resistance among the currently known stainless steels, and it has great potential in the application field of aircraft screw pairs. Because aircraft screws must have both strength and toughness to ensure the safety and long life of the screws. In the existing process, the strength and toughness of the screws cannot be improved at the same time.
[0004] Therefore, how to provide a high-strength and high-toughness lead screw becomes an urgent problem to be solved. Summary of the invention
[0005] In view of the above situation, the present invention aims to provide a pretreatment method for a high-strength and toughness lead screw and a high-strength and toughness lead screw blank, so as to solve the technical problem that the strength and toughness of the existing lead screw cannot be improved at the same time.
[0006] The purpose of the present invention is mainly achieved through the following technical solutions:
[0007] On the one hand, the present invention provides a pretreatment method for a high-strength and tough lead screw, comprising:
[0008] Step 1, keeping the high nitrogen martensitic stainless steel bar at 980-1020° C. and then cooling it to room temperature;
[0009] Step 2, cold treatment at -73±5℃;
[0010] Step 3: Tempering at 550-650° C. to obtain a high-strength and tough lead screw blank.
[0011] Furthermore, in step 1, the holding time t1 and the diameter d of the rod are controlled to meet the following relationship: t1=1.8-2.2d, where d is in millimeters and t1 is in minutes.
[0012] Furthermore, in step 1, oil cooling is used to cool to room temperature.
[0013] Furthermore, the structure of the rod after the treatment in step 1 includes a martensite matrix, residual austenite and a small amount of undissolved carbides.
[0014] Furthermore, the volume fraction of retained austenite is 10% to 20%.
[0015] Furthermore, in step 2, the time t2 of the low temperature cold treatment and the diameter d of the rod meet the following relationship: t2=2.8-3.2d, where d is in millimeters and t2 is in minutes.
[0016] Furthermore, in step 3, the diameter d of the rod is 15-130 cm, and the tempering temperature is 550-595°C.
[0017] Furthermore, in step 3, the insulation time t3 and the diameter d of the rod meet the following relationship: t3=3.8-4.2d, where d is in millimeters and t3 is in minutes.
[0018] Furthermore, in step 3, the diameter d of the rod is greater than 130 cm, and the tempering temperature is 600-650°C.
[0019] The present invention also provides a high-strength and toughness lead screw blank, which is obtained by using the above-mentioned pretreatment method.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] a) The pretreatment method of the high-strength and toughness screw of the present invention can ensure that the structure after quenching includes a martensite matrix, residual austenite and a small amount of undissolved carbides by accurately controlling the quenching temperature, combining low-temperature cold treatment and high-temperature tempering, and the structure after high-temperature tempering is a high-temperature tempered martensite structure matrix mixed with lath ferrite and equiaxed ferrite, and micron-sized carbides are distributed on the matrix. In this way, the high strength and toughness of the screw blank of the present invention are ensured.
[0022] b) The order of the steps in the pretreatment method of the high-strength and toughness lead screw of the present invention and the precise control of the process parameters are key means to ensure the excellent comprehensive performance of the lead screw blank of the present invention. The process parameters need to be coordinated, otherwise the performance cannot be guaranteed.
[0023] c) The high-strength and toughness screw blank obtained by the pretreatment method of the high-strength and toughness screw of the present invention has high strength and toughness. For example, the properties of the high-strength and toughness screw blank with a diameter of 15 to 130 cm are as follows: the core hardness is 38 to 41 HRC, the tensile strength is ≥1150 MPa, and the unnotched impact is ≥150 J; the properties of the high-strength and toughness screw blank with a diameter greater than 130 cm are as follows: the core hardness is 32 to 36 HRC, the tensile strength is ≥1050 MPa, and the unnotched impact is ≥200 J. The high-strength and toughness screw blank of the present invention can be used as a blank for a high-strength and toughness screw.
[0024] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0026] Figure 1 It is the microstructure diagram of Example 1;
[0027] Figure 2 It is the microstructure diagram of Example 3;
[0028] Figure 3 It is the microstructure diagram of Example 5;
[0029] Figure 4 This is the microstructure diagram of Comparative Example 3. DETAILED DESCRIPTION
[0030] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.
[0031] The present invention provides a pretreatment method for a high-strength and tough lead screw, comprising:
[0032] Step 1, keeping the high nitrogen martensitic stainless steel bar at 980-1020° C. and then cooling it to room temperature;
[0033] Step 2, low temperature cold treatment at -73±5℃;
[0034] Step 3: Tempering at 550-650° C. to obtain a high-strength and tough lead screw blank.
[0035] Specifically, in the above step 1, the components of the high nitrogen martensitic stainless steel bar are as follows by mass percentage: C: 0.25% to 0.35%, Si≤1.00%, Mn≤1.00%, Cr: 14.0% to 16.0%, S: ≤0.01%, P: ≤0.02%, Ni≤0.3%, Mo: 0.85% to 1.10%, N: 0.30% to 0.50%, and the remainder is Fe and inevitable trace impurities.
[0036] Specifically, in the above step 1, the high nitrogen martensitic stainless steel bar is smelted by a pressurized electroslag process, and then formed into a bar with a diameter of 15 to 170 mm by high temperature diffusion, hot forging or hot rolling, and heating and softening treatment.
[0037] Specifically, in the above step 1, considering that the insulation temperature is too low, the carbides cannot be fully dissolved into the matrix, resulting in insufficient corrosion resistance and failure to achieve high corrosion resistance; the temperature is too high, the carbides are completely dissolved into the matrix, resulting in coarse original austenite structure and excessive residual austenite after quenching, and the dimensional stability during use cannot be guaranteed. Therefore, the insulation is controlled at 980-1020°C, for example, 990°C, 1000°C, 1005°C, and 1010°C.
[0038] Specifically, in the above step 1, if the holding time is too long, the surface denitrification and decarburization will be serious, resulting in a large amount of processing allowance; if the holding time is too short, it will not be possible to dissolve enough corrosion-resistant elements Cr and N in the matrix, reducing the corrosion resistance. Therefore, the holding time t1 and the diameter d of the rod are controlled to meet the following relationship: t1 = 1.8 ~ 2.2d, d is in millimeters (mm), and t1 is in minutes (min); for example, the holding time is 0.5 ~ 6h.
[0039] Preferably, t1=2d.
[0040] Specifically, in the above step 1, considering that too fast cooling speed may lead to quenching cracking, and too slow cooling speed may lead to insufficient hardness, oil cooling to room temperature is adopted.
[0041] Specifically, the structure of the rod after the treatment in step 1 above includes a martensite matrix, residual austenite and a small amount of undissolved carbides, etc. The volume fraction of the residual austenite is 10% to 20%.
[0042] Specifically, in the above step 2, considering that the low-temperature cold treatment time is too short, resulting in less transformation of residual austenite into martensite, and too long will not achieve complete transformation of residual austenite into martensite, therefore, the low-temperature cold treatment time t2 and the diameter d of the rod are controlled to meet the following relationship: t2 = 2.8 ~ 3.2d, d is in millimeters (mm), and t2 is in minutes (min); for example, the low-temperature cold treatment time is 0.75 ~ 9h.
[0043] Preferably, t2=3d.
[0044] Specifically, in the above step 3, when the diameter d of the rod is 15 to 130 cm, the tempering temperature is 550 to 595°C, and the holding time t3 and the diameter d of the rod meet the following relationship: t3=3.8 to 4.2d, where d is in millimeters (mm) and t3 is in minutes (min); preferably, t3=4d.
[0045] When the diameter d of the rod is greater than 130 cm, the tempering temperature is 600-650°C, and the holding time t4 and the diameter d of the rod meet the following relationship: t4=4.8-5.2d, where d is in millimeters (mm) and t4 is in minutes (min); preferably, t4=5d.
[0046] It should be noted that in the above step 3, if the holding temperature is too low, the martensite will not be fully tempered, resulting in high hardness and strength, but low toughness; if the holding temperature is too high, the martensite will be over-tempered, resulting in low hardness and strength; if the holding time is too long, the hardness and strength will be low, and if the time is too short, the hardness and strength will be high, but the toughness will be low. Therefore, after in-depth research, it is necessary to strictly control the above process parameters to ensure an excellent match between strength and toughness.
[0047] Specifically, the structure of the high-strength and tough lead screw blank with a diameter of 15 to 130 cm obtained after the above step 3 is a high-temperature tempered martensite structure matrix mixed with lath ferrite and equiaxed ferrite, and micron-level carbides are distributed on the matrix; the interlamellar spacing of the lath ferrite is about 0.11 to 0.25 microns, and the particle size of the equiaxed ferrite is about 0.2 to 0.5 microns. The core hardness is 38 to 41 HRC, the tensile strength is ≥1150MPa (for example, 1170 to 1350MPa), and the unnotched impact is ≥150J (for example, 190 to 500J).
[0048] Specifically, the structure of the high-strength and tough lead screw blank with a diameter greater than 130 cm obtained after the above step 3 is a high-temperature tempered martensite mixed with lath ferrite and equiaxed ferrite and micron-sized carbides on this matrix, the interlamellar spacing of the lath ferrite is about 0.2 to 0.4 microns, and the particle size of the equiaxed ferrite is about 0.4 to 0.6 microns. The core hardness is 32 to 36 HRC, the tensile strength is ≥1050 MPa (for example, 1070 to 1150 MPa), and the unnotched impact is ≥200 J (for example, 400 to 500 J).
[0049] Compared with the prior art, the pretreatment method of the high-strength and toughness screw of the present invention can ensure that the structure after quenching includes a martensite matrix, residual austenite and a small amount of undissolved carbides by accurately controlling the quenching temperature, combining low-temperature cold treatment and high-temperature tempering, and the structure after high-temperature tempering is a high-temperature tempered martensite structure matrix mixed with lath ferrite and equiaxed ferrite, and micron-sized carbides are distributed on the matrix, thereby ensuring the high strength and toughness of the screw blank of the present invention.
[0050] The order of the steps in the pretreatment method of the high-strength and toughness lead screw of the present invention and the precise control of the process parameters are key means to ensure the excellent comprehensive performance of the lead screw blank of the present invention. The process parameters need to be coordinated, otherwise the performance cannot be guaranteed.
[0051] The high-strength and toughness screw blank obtained by the pretreatment method of the high-strength and toughness screw of the present invention has high strength and high toughness. For example, the properties of the high-strength and toughness screw blank with a diameter of 15 to 130 cm are as follows: the core hardness is 38 to 41 HRC, the tensile strength is ≥1150 MPa, and the unnotched impact is ≥150 J; the properties of the high-strength and toughness screw blank with a diameter greater than 130 cm are as follows: the core hardness is 32 to 36 HRC, the tensile strength is ≥1050 MPa, and the unnotched impact is ≥200 J. The high-strength and toughness screw blank of the present invention can be used as a blank for a high-strength and toughness screw.
[0052] The advantages of precise control of process parameters of the pretreatment method for high-strength and toughness lead screw of the present invention are demonstrated below with specific embodiments and comparative examples.
[0053] Examples 1-6
[0054] An embodiment of the present invention provides a pretreatment method for a high-strength and tough lead screw. The components of the high-nitrogen martensitic stainless steel bar of the embodiment are, by mass percentage, C: 0.25% to 0.35%, Si≤1.00%, Mn≤1.00%, Cr: 14.0% to 16.0%, S: ≤0.01%, P: ≤0.02%, Ni≤0.3%, Mo: 0.85% to 1.10%, N: 0.30% to 0.50%, and the remainder is Fe and inevitable trace impurities.
[0055] The preparation method of the pretreatment method of the high-strength and toughness lead screw of Example 1 comprises:
[0056] Step 1, heat a high nitrogen martensitic stainless steel bar with a diameter of Φ15 mm at 980° C. for 0.5 h and then oil cool it to room temperature;
[0057] Step 2, low temperature cold treatment at -73°C for 0.75h;
[0058] Step 3: Tempering at 550°C for 1 hour to obtain a high-strength and tough lead screw blank.
[0059] The matrix of the rod material after the treatment in step 1 is martensite, and the matrix contains about 10% of residual austenite and a small amount of undissolved carbides.
[0060] The microstructure of the high-strength and tough lead screw blank prepared by the method of this embodiment is a high-temperature tempered martensite mixed with lath ferrite and equiaxed ferrite + micron-sized carbides on the matrix, and the interlamellar spacing of the lath ferrite is about 0.13 to 0.16 microns. The particle size of the equiaxed ferrite is about 0.27 to 0.32 microns. The properties of the high-strength and tough lead screw blank of this embodiment are shown in Table 1 below.
[0061] Example 2
[0062] The components of the high nitrogen martensitic stainless steel of this embodiment are the same as those of Embodiment 1, and will not be described again.
[0063] The preparation method of the pretreatment method of the high-strength and toughness lead screw of Example 2 includes:
[0064] Step 1, heat a high nitrogen martensitic stainless steel bar with a diameter of Φ40 mm at 1000° C. for 80 minutes and then oil cool it to room temperature;
[0065] Step 2, low temperature cold treatment at -73°C for 120 min;
[0066] Step 3: Tempering at 580°C for 160 min to obtain a high-strength and tough lead screw blank.
[0067] The matrix of the rod after the treatment in step 1 is martensite, which contains about 14% of residual austenite and a small amount of undissolved carbides.
[0068] The microstructure of the high-strength and tough lead screw blank prepared by the method of this embodiment is a high-temperature tempered martensite mixed with lath ferrite and equiaxed ferrite + micron-sized carbides on the matrix, the lamellar spacing of the lath ferrite is about 0.16 to 0.2 microns, and the particle size of the equiaxed ferrite is about 0.33 to 0.37 microns. The properties of the high-strength and tough lead screw blank of this embodiment are shown in Table 1 below.
[0069] Example 3
[0070] The components of the high nitrogen martensitic stainless steel of this embodiment are the same as those of Embodiment 1, and will not be described again.
[0071] The preparation method of the pretreatment method of the high-toughness lead screw of Example 3 comprises:
[0072] Step 1, heat a high nitrogen martensitic stainless steel bar with a diameter of Φ60 mm at 1020° C. for 2 hours and then oil cool it to room temperature;
[0073] Step 2, low temperature cold treatment at -73°C for 3h;
[0074] Step 3: Tempering at 590°C for 4 hours to obtain a high-strength and tough lead screw blank.
[0075] The matrix of the rod material after the treatment in step 1 is martensite, and the matrix contains about 18% of residual austenite and a small amount of undissolved carbides.
[0076] The microstructure of the high-strength and tough lead screw blank prepared by the method of this embodiment is a high-temperature tempered martensite mixed with lath ferrite and equiaxed ferrite + micron-sized carbides on the matrix, the lamellar spacing of the lath ferrite is about 0.18 to 0.21 microns, and the particle size of the equiaxed ferrite is about 0.38 to 0.42 microns. The properties of the high-strength and tough lead screw blank of this embodiment are shown in Table 1 below.
[0077] Example 4
[0078] The components of the high nitrogen martensitic stainless steel of this embodiment are the same as those of Embodiment 1, and will not be described again.
[0079] The preparation method of the pretreatment method of the high-strength and toughness lead screw of Example 4 comprises:
[0080] Step 1, heat a high nitrogen martensitic stainless steel bar with a diameter of Φ90 mm at 1020° C. for 3 hours and then oil cool it to room temperature;
[0081] Step 2, low temperature cold treatment at -73°C for 4.5h;
[0082] Step 3: Tempering at 595°C for 6 hours to obtain a high-strength and tough lead screw blank.
[0083] The matrix of the rod material after the treatment in step 1 is martensite, and the matrix contains about 18% of residual austenite and a small amount of undissolved carbides.
[0084] The microstructure of the high-strength and tough lead screw blank prepared by the method of this embodiment is a high-temperature tempered martensite mixed with lath ferrite and equiaxed ferrite + micron-sized carbides on the matrix, the lamellar spacing of the lath ferrite is about 0.19 to 0.22 microns, and the particle size of the equiaxed ferrite is about 0.38 to 0.42 microns. The properties of the high-strength and tough lead screw blank of this embodiment are shown in Table 1 below.
[0085] Example 5
[0086] The components of the high nitrogen martensitic stainless steel of this embodiment are the same as those of Embodiment 1, and will not be described again.
[0087] The preparation method of the pretreatment method of the high-strength and toughness lead screw of Example 1 comprises:
[0088] Step 1, heat a high nitrogen martensitic stainless steel bar with a diameter of Φ130 mm at 1020° C. for 260 min and then oil cool it to room temperature;
[0089] Step 2, low temperature cold treatment at -73°C for 390 min;
[0090] Step 3: Tempering at 595°C for 520 min to obtain a high-strength and tough lead screw blank.
[0091] In the structure of the rod after the treatment in step 1 above, the matrix is martensite, which contains about 20% of residual austenite and a small amount of undissolved carbides.
[0092] The microstructure of the high-strength and tough lead screw blank prepared by the method of this embodiment is a high-temperature tempered martensite mixed with lath ferrite and equiaxed ferrite + micron-sized carbides on the matrix, the lamellar spacing of the lath ferrite is about 0.18 to 0.22 microns, and the particle size of the equiaxed ferrite is about 0.41 to 0.45 microns. The properties of the high-strength and tough lead screw blank of this embodiment are shown in Table 1 below.
[0093] Example 6
[0094] The components of the high nitrogen martensitic stainless steel of this embodiment are the same as those of Embodiment 1, and will not be described again.
[0095] The preparation method of the pretreatment method of the high-strength and toughness lead screw of Example 1 comprises:
[0096] Step 1, heat a high nitrogen martensitic stainless steel bar with a diameter of Φ170 mm at 1020° C. for 340 min and then oil cool it to room temperature;
[0097] Step 2, low temperature cold treatment at -73°C for 510 minutes;
[0098] Step 3: Tempering at 650°C for 850 min to obtain a high-strength and tough lead screw blank.
[0099] The matrix of the rod material after the treatment in step 1 is martensite, which contains about 20% of residual austenite and a small amount of undissolved carbides.
[0100] The microstructure of the high-strength and tough lead screw blank prepared by the method of this embodiment is a high-temperature tempered martensite mixed with lath ferrite and equiaxed ferrite + micron-sized carbides on the matrix, the lamellar spacing of the lath ferrite is about 0.24 to 0.28 microns, and the particle size of the equiaxed ferrite is about 0.55 to 0.61 microns. The properties of the high-strength and tough lead screw blank of this embodiment are shown in Table 1 below.
[0101] The inventor has conducted a lot of research during the research process, and now uses some solutions with poor performance as comparative examples.
[0102] Comparative Example 1
[0103] This comparative example provides a method for pretreating a lead screw, the components of which are the same as those in Example 1 and will not be described in detail herein. The method is substantially the same as that in Example 1, except that:
[0104] Step 1, cooling the high nitrogen martensitic stainless steel bar to room temperature after keeping it at 1040°C;
[0105] There is nearly 30% of retained austenite in the structure of the rod after the treatment in step 1 above.
[0106] The microstructure of the screw blank prepared by the method of this comparative example has a blocky pearlite structure. The properties of the screw blank of this comparative example are shown in Table 1 below.
[0107] Comparative Example 2
[0108] This comparative example provides a method for pretreating a lead screw, and its components are the same as those in Example 1, which will not be described in detail here. The method is substantially the same as that in Example 1, except that:
[0109] Step 3: Tempering treatment at 700°C for 160 minutes, resulting in a hardness of less than 25HRC and a tensile strength of less than 1000MPa.
[0110] In the microstructure of the screw blank prepared by the method of this comparative example, the martensite has completely degenerated into equiaxed ferrite and equiaxed carbide, resulting in low hardness and strength. The properties of the screw blank of this comparative example are shown in Table 1 below.
[0111] Comparative Example 3
[0112] This comparative example provides a method for pretreating a lead screw, the components of which are the same as those in Example 2, and will not be described in detail herein. The method is substantially the same as that in Example 2, except that:
[0113] Step 3: Tempering treatment at 500°C for 240 minutes results in a hardness higher than 50HRC and a tensile strength higher than 1500Mpa, but an impact toughness of only 30J.
[0114] The tempered martensite in the microstructure of the screw blank prepared by the method of this comparative example is mainly a strip martensite structure and fine carbides. The properties of the screw blank of this comparative example are shown in Table 1 below.
[0115] Table 1 Performance results of examples and comparative examples
[0116] Sample No. Room temperature hardness / HRC Tensile strength / MPa Impact performance / J Example 1 40.9 40.4 40.5 40.4 40.5 1310 1332 231 194 226 Example 2 39.8 39.1 39.3 39.2 40.1 1275 1285 285 269 281 Example 3 38.1 38.4 39.0 38.1 39.2 1235 1245 310 363 347 Example 4 38.2 38.5 38.3 38.1 38.6 1170 1178 410 450 442 Example 5 38.1 38.2 38.2 39.1 38.5 1175 1185 471 494 426 Example 6 33.9 33.4 33.4 33.2 32.4 1075 1085 469 481 495 Comparative Example 1 40.3 40.1 40.2 41.4 40.0 1410 1432 131 114 126 Comparative Example 2 22.4 21.4 20.4 20.5 20.5 775 785 491 483 492 Comparative Example 3 50.5 50.4 50.4 50.2 50.4 1575 1585 31 52 70
[0117] Note: When the diameter is 15-130cm, the performance requirements are room temperature hardness 38-41HRC, tensile strength ≥1150MPa, and impact performance ≥150J.
[0118] When the diameter is greater than 130cm, the performance requirements are room temperature hardness of 32-36HRC, tensile strength of ≥1050MPa, and impact performance of ≥200J.
[0119] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A pretreatment method for a high-strength and tough lead screw, characterized in that: include: Step 1, keeping the high nitrogen martensitic stainless steel bar at 980-1020° C. and then cooling it to room temperature; Step 2, cold treatment at -73±5℃; Step 3: Tempering at 550-650° C. to obtain a high-strength and tough lead screw blank.
2. The pretreatment method of the high-strength and tough lead screw according to claim 1, characterized in that: In step 1, the holding time t1 and the diameter d of the rod are controlled to meet the following relationship: t1=1.8~2.2d, the unit of d is millimeter, and the unit of t1 is minute.
3. The pretreatment method of the high-strength and tough lead screw according to claim 1, characterized in that: In the step 1, oil cooling is used to cool to room temperature.
4. The pretreatment method of a high-strength and tough lead screw according to claim 1, characterized in that: The structure of the rod after the treatment in step 1 includes a martensite matrix, residual austenite and a small amount of undissolved carbides.
5. The pretreatment method of the high-strength and tough lead screw according to claim 4, characterized in that: The volume fraction of the retained austenite is 10% to 20%.
6. The pretreatment method of a high-strength and tough lead screw according to claim 1, characterized in that: In step 2, the low temperature cold treatment time t2 and the diameter d of the rod meet the following relationship: t2=2.8~3.2d, the unit of d is millimeter, and the unit of t2 is minute.
7. The pretreatment method of a high-strength and tough lead screw according to claim 1, characterized in that: In step 3, the diameter d of the rod is 15 to 130 cm, and the tempering temperature is 550 to 595°C.
8. The method for pretreating a high-strength and tough lead screw according to claim 7, characterized in that: In step 3, the holding time t3 and the diameter d of the rod meet the following relationship: t3=3.8~4.2d, the unit of d is millimeter, and the unit of t3 is minute.
9. The method for pretreating a high-strength and tough lead screw according to claim 1, characterized in that: In step 3, the diameter d of the rod is greater than 130 cm, and the tempering temperature is 600-650°C.
10. A high-strength and tough lead screw blank, characterized in that: The high-strength and toughness lead screw blank is obtained by the pretreatment method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Mo-containing high hardness stainless steel, and heating processing technology, and forming member
CN110656293A
Heat treatment process for high-nitrogen stainless bearing steel
CN112680574A
High-nitrogen martensitic stainless steel surface nitriding hardening method and high-nitrogen martensitic stainless steel
CN117626166A
High-nitrogen martensitic stainless steel with high corrosion resistance and fatigue resistance and preparation method of high-nitrogen martensitic stainless steel
CN118308579A